2018
DOI: 10.1017/9781316795897
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Mantle Dynamics

Abstract: Geodynamics is the study of the deformation and flow of the solid Earth and other planetary interiors. Focusing on the Earth's mantle, this book provides a comprehensive, mathematically advanced treatment of the continuum mechanics of mantle processes and the craft of formulating geodynamical models to approximate them. Topics covered include slow viscous flow, elasticity and viscoelasticity, boundary-layer theory, long-wave theories including lubrication theory and shell theory, two-phase flow, and hydrodynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 327 publications
(512 reference statements)
0
8
0
Order By: Relevance
“…Following Ribe (2018), we refer to a viscous shell as a sheet. Our model lithosphere can be considered as a shallow sheet if its “midsurface departs from a reference plane by an amount much smaller than its principal radii of curvature” (Ribe, 2018). To estimate the midsurface departure, we consider the chord, with length C , as the reference plane and the arc, with length A , as the curved midsurface (Figure 2a).…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Following Ribe (2018), we refer to a viscous shell as a sheet. Our model lithosphere can be considered as a shallow sheet if its “midsurface departs from a reference plane by an amount much smaller than its principal radii of curvature” (Ribe, 2018). To estimate the midsurface departure, we consider the chord, with length C , as the reference plane and the arc, with length A , as the curved midsurface (Figure 2a).…”
Section: Modelmentioning
confidence: 99%
“…Therefore, the lithosphere in our model can be considered as a shallow sheet. Consequently, the differences in stress and velocity between a flat lithosphere and a curved lithosphere are likely in the order of the value of H / L ≈ 0.1 (e.g., Ribe, 2018). Hence, we do not expect significant differences between the results of a flat and curved lithosphere.…”
Section: Modelmentioning
confidence: 99%
“…They determined the existence of an analytical solution for a particular class of non‐Newtonian fluid. Ribe [ 3 ] also studied the self‐similarity in a system with flow and heat transfer. This study identified two regions susceptible to self‐similar transformation depending on the Raleigh number.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Beyond the governing equations, the Stokes-Rayleigh analogy also applies to the solutions to boundary value problems if the boundary conditions themselves are analogous [Ribe, 2018]. In the case of interest here, the Stokes-Rayleigh analogy predicts for an incompressible body that elastic isostasy with zero surface (resp.…”
Section: Stokes-rayleigh Analogymentioning
confidence: 99%